IDENTIFICATION OF INDUCED DRAFT FAN (IDF) DAMAGE IN BOILER WASTE GAS SYSTEM - Yasdin Yasdin; alimin alimin; Siti Ramasih (Universitas Sultan Ageng Tirtayasa, 2019)
Induced Draft Fan (IDF) is a fan that sucks air from inside the boiler out to the chimney, producing negative pressure on the boiler, keeping the circulation of combustion air in the boiler normal. IDF is one of the main components in the exhaust gas system which serves to maintain the temperature and vacuum of the furnace in the boiler. This report will identify IDF damage using vibration indication control instruments by looking at vibration indication trending data through the Distributed Control System (DCS) in the Central Control Room (CCR). The results of the trending data will then be identified whether the vibration in Induced Draft Fan has increased, if the vibration ≥ 5.6 mm/s is declared an alarm and if the vibration ≥ 7.1 mm/s then the unit trip or must be stopped. Based on the results of research during industrial practice in Banten 2 PLTU Labuan there were 2 conditions in the IDF, namely when there was a disturbance with a height of X and Y side vibrations of 22.5 mm/s, and conditions after improvement with the height of X vibration side that is, an average of 4.2 mm/s and Y side averaging 4.1 mm/s. The high vibration is affected by the damage of several IDF components, caused by the amount of ash remaining combustion that enters the IDF which causes abrasion of the impeller blade.